Doctrine of Trinity: A Theological Approach of Evidence of The Trinity in The New Testament - Astika, Made (Sekolah Tinggi Theologia Jaffray, 2012)
The doctrine of the Trinity has been a divisive issue throughoutthe entire history of the Christian church. While the core aspects of theTrinity are clearly presented in God’s Word, some of the side issues arenot as explicitly clear. The Father is God, the Son is God, and the HolySpirit is God—but there is only one God. That is the biblical doctrine ofthe Trinity. Beyond that, the issues are, to a certain extent, debatable andnon-essential. Rather than attempting to fully define the Trinity withour finite human minds, we would be better served by focusing on thefact of God's greatness and His infinitely higher nature.From the Second Century to our present age many people havefound the biblical doctrine of the Trinity hard to understand. Someonehas said of this doctrine: “Try to explain it, and you’ll lose your mind; buttry to deny it, you’ll lose your soul.